Analysis of Factors that Influence First Year Students to Choose Biology Education Study Program in UniversitasTidar - Muhammad Radian Nur Alamsyah; Aprita Nur Rahmadany (Indonesian Journal of Biology Education, 2018)
This study aimed to determine the factors that influence first year students to choose Biology Education study program in Universitas Tidar and further discover the dominant one. Survey used as a data collection method in this study with population included all 90 first year students of Biology Education study program in Universitas Tidar in 2018. Sample size in this research is 74 students which is determined by Slovin formula. This research’s data was collected using closed model Likert scale questionaires and then analyzed descriptively and factor analysis exploratory using SPSS 22.00 for windows. The results showed that there are four factors that influence first year students to choose Biology Education study program in Universitas Tidar: (1) campus condition (with variables encompass: tuition fee, campus administrator, and campus location); (2) self motivation (including variables: interest, future goals, and talent); (3) campus attractiveness (consists of variables: career opportunity, campus facilities, and campus promotion); and (4) reference group (with variable: parents and friends influence). Campus condition factor was found as the most dominant factor while interest as the most dominant variable.